Charissa Endar receives Puspanita Community Care Award - Noraini, Yusoff (UMPSA, 2024)
GAMBANG, 26 October 2024 – Bachelor of Business Engineering with Honours graduate Charissa Endar, 24, received the Puspanita Community Care Award at the 19th Convocation Ceremony of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), held at the Sports Complex Hall, UMPSA Gambang Campus.